The effect of Covid-19 on the mental health of the people in the Indian subcontinent: A scoping review - Kabir, Russell; Bai, Ancy Chandrababu Mercy; Syed, Haniya Zehra; Hasan, Md Rakibul; Vinnakota, Divya; Kar, Sujita Kumar; Singh, Rakesh; Sathian, Brijesh; Arafat, S.M. Yasir (Nepal Journal of Epidemiology, 2023)
Background: Indian subcontinent has high mental heath burden and low resoueces to cope the mental health challenges. Assessment of impact of Covid-19 pandemic on the mental mental healthwould help to prioratize the resource allocations. We aimed to assess the impact of COVID-19 on the mental health of people in the Indian subcontinent. Methods: We followed PRISMA guidelines and made a systematic serach in PubMed, Scopus, and Embase to identify the original studies assessing mental health conditions during Covid-19 pandemic in the Indian subcontinent. Results: A total of 34 studies carried out between 2020 and 2022 was included in this review. The prevalence of anxiety disorders varied widely starting from 2.5% among residents of urban slum in North India to 53% Bangladesh, 21.7% in Pakistan. The prevalence of depression also varied widely starting from 3.5% North India to 29.8% in Pakistan. The prevalence of stress related problem varied from 18.3% in Pakistan to 59.7% in Bangladesh. Female gender, married status, health care workers, and mental illness were the important predicotrs for anxiety and depressive disorders. Conclusion: The impact of Covid-19 pandemic on mental health of people living in Indian subcontinent varies widely based on study population and methods.Therefore, a cautious interpretation is needed while generalizing the study results.